The Influence of Service Quality and Price on Consumer Loyalty at Mie Gacoan Pancing (Case Study of Management Study Program Students at UNIMED) - Putra, Irwansyah Putra; Monalisa, Indah; Nasution, Risky Alhaq; Rinaldi, Muammar; Sienny (Outline Publisher, 2025)
This study aims to analyze the influence of service quality and price on consumer loyalty at Mie Gacoan Pancing. The research method used is quantitative with a multiple linear regression approach. Data were collected through a questionnaire that has been tested for validity and reliability. The results show that service quality has a positive and significant effect on consumer loyalty, while price has no significant effect. Simultaneously, both independent variables have a significant effect on consumer loyalty with a contribution of 50.4%. The implication of this study is that the management of Mie Gacoan Pancing should further improve service quality to increase customer loyalty.